Incremental Pattern Matching in Graph-Based State Space Exploration - Ghamarian, AmirHossein; Jalali, Arash; Rensink, Arend (Electronic Communications of the EASST, 2011)
Graph pattern matching is among the most costly operations in any graph transformation system. Incremental pattern matching aims at reducing this cost by incrementally updating, as opposed to totally recalculating, the possible matches of rules in the graph grammar at each step of the transformation. In this paper an implementation of one such algorithm is discussed with respect to the GROOVEtoolset, with a special emphasis put on state space exploration. Specifically, we shall discuss exploration strategies that could better harness the positive aspects ofincremental pattern matching in order to gain better performance.